A ANESTHESIA FOR AWAKE CRANIOTOMY – HOW DO WE PERFORM IT? Anesthesia for awake craniotomy - Nastasovic, Tijana; Savic, Nevena; Lazic, Igor; Ivosevic, Tjasa; Bogdanovic, Ivan; Ilic, Rosanda; Milisavljevic, Filip (Medical Research, 2024)
Awake craniotomy is a neurosurgical procedure that is used for the safe removal of intracranial lesions near Broca’s and Wernicke’s speech areas. During it, speech mapping is done. Its use demands anesthesia for awake craniotomy, which includes different possibilities for the management of anesthesia with awake patients at the moment of tumor removal. There are two widely accepted concepts: „awake-awake-awake“, when the patient is consciously sedated („awake“) all the time during surgery, with lighter or deeper sedation (monitored anesthesia care), or „asleep-awake-asleep“, when the patient is introduced into general endotracheal anesthesia while opening the skull, but awake during lesion removal and asleep during closure. Our protocol is a form of „asleep-awake“ concept, with general endotracheal anesthesia for craniotomy and awake patients during and after lesion removal (including skull closure).